Major Stressors and Coping Strategies of Internal Migrant Workers During the COVID-19 Pandemic: A Qualitative Exploration - Srivastava, Akanksha; Arya, Yogesh Kumar; Joshi, Shobhna; Singh, Tushar; Kaur, Harleen; Chauhan, Himanshu; Das, Abhinav (Frontiers in Psychology, 2021)
COVID-19 forced lockdown in India, leading to the loss of job, crisis of food, and other financial catastrophes that led to the exodus migration of internal migrant workers, operating in the private sector, back to their homes. Unavailability of transport facilities led to an inflicted need to walk back to homes barefooted without lack of any other crucial resources on the way. The woeful state of internal migrant workers walking back, with all their stuff on their back, holding their children, was trending on social media worldwide. Their problem continued even after reaching home, including misbehavior of villagers, indifferent mannerism of family members toward them, inability to fulfill family responsibility, and financial crisis, which led to stress, fear, and trauma for these internal migrant workers. The present paper aimed to assess the idiosyncratic stressors of internal migrant workers throughout the pandemic era and their responses toward those problems, which helped them cope with it. In-depth semistructured telephonic interviews were conducted with 25 internal migrant workers who were working in different cities in India before lockdown. The analyses revealed that multiple stressors include financial crisis, unavailability of food, inability to continue education, inability to pay house rent, lack of support from neighbors and family, and other psychological stressors that affected them. However, they also tried multiple strategies to deal with the problems, including a cognitive appraisal of the problem and making oneself psychologically competent to deal with the situation. Social support of family and friends played a vital role in enhancing hardiness and increasing the level of happiness at scarce times. At the same time, some of them could not deal with stressors and opted for psychiatric help to manage the physical symptoms of stress.